Assessment of the territorial development of agricultural land use in Ukraine - Kupriyanchyk, I.; Butenko, E.; Kolisnyk, G. (Land Management, Cadastre and Land Monitoring, 2020)
The article explores the prospects of territorial development of agricultural land use in Ukraine. It has been established that land resources, namely agricultural lands, are one of the main agricultural production resources required for crop production, including livestock production. It is concluded that the efficiency of agricultural land, distribution between land users, depends on the efficiency of agricultural production as a whole. It is emphasized that the emphasis of the state policy in the agrarian sphere on the accelerated and insufficiently motivated privatization of land and property caused the destruction of large commodity agricultural production, but was not effective in the formation of new productive production forms. It was emphasized that with the change of economic forms the boundaries of land use, the size of land were changed, which leads to difficulties in their cultivation and implementation of measures for their protection. For example, in connection with the creation of a large number of farms, there was a significant fragmentation of land, which in turn led to excessive parceling of land and, in particular, to a decrease in the efficiency of agricultural production. Keywords: economic development, environmental factors, territorial development, agricultural land use, agricultural land.